Bioluminescent Sensors for Ca++ Flux Imaging and the Introduction of a New Intensity-Based Ca++ Sensor - Yang, Jie; Johnson, Carl Hirschie (Frontiers in Bioengineering and Biotechnology, 2021)
Sensitive detection of biological events is a goal for the design and characterization of sensors that can be used in vitro and in vivo. One important second messenger is Ca++ which has been a focus of using genetically encoded Ca++ indicators (GECIs) within living cells or intact organisms in vivo. An ideal GECI would exhibit high signal intensity, excellent signal-to-noise ratio (SNR), rapid kinetics, a large dynamic range within relevant physiological conditions, and red-shifted emission. Most available GECIs are based on fluorescence, but bioluminescent GECIs have potential advantages in terms of avoiding tissue autofluorescence, phototoxicity, photobleaching, and spectral overlap, as well as enhancing SNR. Here, we summarize current progress in the development of bioluminescent GECIs and introduce a new and previously unpublished biosensor. Because these biosensors require a substrate, we also describe the pros and cons of various substrates used with these sensors. The novel GECI that is introduced here is called CalBiT, and it is a Ca++ indicator based on the functional complementation of NanoBiT which shows a high dynamic change in response to Ca++ fluxes. Here, we use CalBiT for the detection of Ca++ fluctuations in cultured cells, including its ability for real-time imaging in living cells.